1997
DOI: 10.1192/bjp.171.1.42
|View full text |Cite
|
Sign up to set email alerts
|

One hundred cases of attempted suicide in the elderly

Abstract: Elderly people who attempt suicide have a high mortality both from completed suicide and death from other causes. The completed suicide rate is at least 1.5% per year, and the repetition rate is 5.4% per year. Those at risk of further self-harm are likely to be in contact with psychiatric services and to be suffering from persistent depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
100
4
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(122 citation statements)
references
References 14 publications
(6 reference statements)
15
100
4
3
Order By: Relevance
“…Suicidal ideation and pessimistic thoughts are not uncommon among acutely medically ill and continuing-care geriatric in-patients, necessitating the training of staff in these facilities in the recognition and treatment of underlying disorders (Shah et al,1998) These general findings for completed suicide have their parallel in findings from studies of elderly people who attempted suicide. Hepple & Quinton (1997), for example, found 53% of a series of 100 consecutive people who attempted suicide to be suffering from significant physical illness at index assessment following the attempt. Follow-up data revealed a mortality from natural causes of 8.6% per year, representing an increase of 1.6:1 compared with the age-and gender-matched population.…”
Section: Physical Illnessmentioning
confidence: 99%
“…Suicidal ideation and pessimistic thoughts are not uncommon among acutely medically ill and continuing-care geriatric in-patients, necessitating the training of staff in these facilities in the recognition and treatment of underlying disorders (Shah et al,1998) These general findings for completed suicide have their parallel in findings from studies of elderly people who attempted suicide. Hepple & Quinton (1997), for example, found 53% of a series of 100 consecutive people who attempted suicide to be suffering from significant physical illness at index assessment following the attempt. Follow-up data revealed a mortality from natural causes of 8.6% per year, representing an increase of 1.6:1 compared with the age-and gender-matched population.…”
Section: Physical Illnessmentioning
confidence: 99%
“…16 Outro importante complicador dos quadros depressivos é o maior risco de suicídio -depressão está claramente presente em pelo menos 50% dos casos letais de suicídio em idosos. 17 19 observaram que a prevalência de mania em indivíduos vivendo na comunidade é baixa (0,6% dos 3.258 de uma cidade canadense), e que em 95% desses casos o primeiro episódio de transtorno de humor ocorreu antes dos 26 anos de idade. Assim, a maioria dos casos de mania em idosos representam apenas uma fase de um transtorno de humor que se iniciou vários anos antes na vida do paciente.…”
Section: Método E Análise Dos Dadosunclassified
“…Having one or more chronic conditions was also associated with wishing for death among men and women [36]. Suicide has been estimated to be a risk factor that is particularly salient in men [37]. However, Lebret et al [38] found that an elderly person who attempts suicide was most likely to be a widow suffering from social isolation, loneliness, and depression.…”
Section: Discussionmentioning
confidence: 99%